LIDAR for atmosphere Research over Africa: A trilateral research programme (LARA-TRIP) - (:unkn) unknown (My University, 2008)
This paper describes the importance of LIDAR for atmosphere research over Africa and the initiatives being undertaken to foster such research. A mobile LIDAR system is to be employed for field campaign measurements over different locations around South Africa and Africa.
Keywords: African Research